PHYLOGENESIS AND THE SYSTEM OF THE CAMBRIAN UNIVALVED MOLLUSKS - Parkhaev P.Yu. (My University, 2002)
The history of the study and the development of ideas about the systematic position of the Cambrian univalved mollusks is reviewed. On the basis of the functional morphology of shells (Parkhaev, 2000a, 2001a), the phylogenetic scenario of the evolution of the group is reconstructed and its systematics is determined. Several new taxa are described, i.e., Archaeobranchia subclas. nov., Khairkhaniiformes ordo nov., Igarkiellidae fam. nov., Trenellidae fam. nov., Watsonellinae subfam. nov., and Runnegarella gen. nov.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская